2014
DOI: 10.1007/s00431-013-2252-8
|View full text |Cite
|
Sign up to set email alerts
|

Two Japanese familial cases of Caffey disease with and without the common COL1A1 mutation and normal bone density, and review of the literature

Abstract: The results reveal that Caffey disease is genetically heterogeneous and that affected and unaffected adult patients with or without the common COL1A1 mutation have normal bone mineral density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…CMO is clinically equivalent to human infantile cortical hyperostosis [ 10 , 15 ]. A common missense variant in COL1A1 has been found in several patients with an autosomal dominant condition with incomplete penetrance [ 16 , 17 ]. Interestingly, the mechanism how the defected collagen leads to self-limiting hyperostotic bone lesions is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CMO is clinically equivalent to human infantile cortical hyperostosis [ 10 , 15 ]. A common missense variant in COL1A1 has been found in several patients with an autosomal dominant condition with incomplete penetrance [ 16 , 17 ]. Interestingly, the mechanism how the defected collagen leads to self-limiting hyperostotic bone lesions is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We can therefore confidently state that the S185 individual presented only the wild‐type allele at the c.3040 position, and the etiological cause of the disease in our sample patient could not be proved with certainty. However, genetic heterogeneity of ICH has already been suggested in living patients (Gensure et al, ; Kitaoka et al, ), although no other candidate ICH genes have been identified to date. For this reason, we cannot exclude a diagnosis of ICH on the basis of the molecular results.…”
Section: Discussionmentioning
confidence: 99%
“…This finding places ICH within the group of type 1 collagen-related conditions, such as osteogenesis imperfecta and Ehlers-Danlos syndrome. 5 Following this report, patients with ICH expressing the COL1A1 mutation were reported worldwide, [6][7][8][9][10][11] and even one lethal prenatal genetic case of ICH was described. 12 Interestingly, in several ICH patients, this previously known mutation in COL1A1 was not identified nor were other novel mutations found for this gene.…”
Section: Introductionmentioning
confidence: 88%
“…12 Interestingly, in several ICH patients, this previously known mutation in COL1A1 was not identified nor were other novel mutations found for this gene. 4,11 Some cases of ICH were suggested to be sporadic rather than genetic and were thought to differ from the familial form, as can sometimes be attributed to exposure to prostaglandin E1 and prostaglandin E2. 13,14 It was also hypothesized that ICH might have an autosomal-recessive inheritance form [15][16][17] ; nevertheless, no specific mutation has so far been described.…”
Section: Introductionmentioning
confidence: 99%